Vegetation and plant exploitation at Mentesh Tepe (Azerbaijan), 6th–3rd millennium BC initial results of the archaeobotanical study. (22nd February 2016) - Decaix, Alexia; Messager, Erwan; Tengberg, Margareta; Neef, Reinder; Lyonnet, Bertille; Guliyev, Farhad
Abstract: The study of several types of botanical remains from the site of Mentesh Tepe, Azerbaijan, has provided the first data on the vegetation cover and the exploitation and use of plant resources from the Neolithic to the Early Bronze Age in this part of the Kura River Basin. Riparian woodlands constitute the main fuel source throughout the occupational sequence. However, wood was also exploited in relatively open woodlands characterised by the presence of a dozen shrub and tree species, among them oak, hornbeam, buckthorn, wayfaring-tree, maple and lime. Most seed and fruit remains correspond either to crops, such as cereals (barley, wheat) and pulses (lentil, grass pea), or to weeds and ruderal plants. The analysis of phytoliths shows that cereals were treated (de-husked) on-site. Very few fruits were found in the botanical record.